An ethylenediamine-grafted Y zeolite: a highly regenerable carbon dioxide adsorbent via temperature swing adsorption without urea formation. Issue 5 (4th April 2016) - Kim, Chaehoon; Cho, Hae Sung; Chang, Shuai; Cho, Sung June; Choi, Minkee
Abstract : An ethylenediamine-grafted Y zeolite effectively adsorbs CO2 from a wet flue gas and it is highly regenerable through a temperature swing adsorption (TSA) process. Abstract : Solid adsorbents including amine-functionalized porous materials and zeolites have been extensively investigated for post-combustion CO2 capture. Amine-functionalized porous materials have shown highly promising CO2 uptake in a wet flue gas, but suffer from significant amine deactivation due to urea formation under desorption conditions ( e.g., desorption under 100% CO2 at >130 °C) of temperature swing adsorption (TSA) cycles. In contrast, purely inorganic zeolites are thermochemically stable but cannot adsorb CO2 from a wet flue gas because of the preferential H2 O adsorption. In the present work, we synthesized an ethylenediamine-grafted Y zeolite, which can synergistically combine the strengths of both adsorbent systems. The amine groups can effectively capture CO2 in a wet flue gas, while the strongly co-adsorbed H2 O within the hydrophilic zeolite micropores suppresses urea formation (dehydration reaction between amines and CO2 ) under desorption conditions according to Le Chatelier's principle. The organic–zeolite hybrid adsorbent retains working capacities higher than 1.1 mmol g −1 over 20 TSA cycles. Because the adsorbent is prepared from a commercially available zeolite, it is also highly cost efficient and suitable for mass production.